"I Just Wanted to Die": Preprison and Current Suicide Ideation Among Women Serving Life Sentences. (August 2013) - Dye, Meredith Huey; Aday, Ronald H.
For women serving life sentences, adjustments to prison are often marked by thoughts of suicide. Many enter prison with specific vulnerabilities that place them at risk for suicide. Using data on 214 female lifers, the authors examined the extent of suicide ideation prior to incarceration as well as current suicide ideation. The relationships between preprison abuse, mental health indicators, prison adjustment factors, prison and family supports, and time served along with sociodemographic variables were analyzed with respect to four categories of preprison and current suicide ideation. Multinomial logistic regression results indicated significant group differences in suicide ideation for abuse histories, depression, family and prison supports, and education level. Among the preprison ideation groups, current depression—not abuse history—distinguished between women with or without current ideation. That is, the way women coped with past abuse was a stronger predictor of current suicide ideation than abuse itself.